The QOS Analysis in L2TP/IPSEC VPN Network at Bimba Y Lola Boutique - Wadih M Hatta (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The development of Internet network technology is accompanied by an increase in the risk of attacks on the security of the Internet network itself. As a preventive measure, PT. Trans Fashion Indonesia implements the IPSec (Internet Protocol Security) protocol to complement the VPN (Virtual Private Network) security protocol on its boutique internet network. This protocol is expected to provide good security without reducing the quality of internet services. The author's research was conducted for QOS (Quality of Service) analysis of internet network quality by measuring packet loss, delay, jitter, and throughput referring to the Telecommunications and Internet Protocol Harmonization Over Network (TIPHON) standard. The object of research is the internet network at the Bimba Y Lola Boutique which is the newest boutique owned by PT. Trans Fashion Indonesia. The study results show that the internet network quality at the Bimba Y Lola boutique is good. With a Packet loss value = 0.5% or data loss close to zero, a delay of 7.8 ms with a very good value, jitter = 0.1 ms with an index of 4 or good, and throughput = 177/kbits/s. Based on the results of this study, the authors conclude that the implementation of the L2TP/IPSec VPN protocol provides protection for network security without reducing the quality of the network.